Developing Social Integration of Santri with Special Needs Through the Isma Learning Therapy School (ILTS) Curriculum - Sari, Fidiyah; Siti Risda Sakila; Bono Setyo; Suria Hani A. Rahman (Edukasia Islamika : Jurnal Pendidikan Islam, 2024)
Inclusive education is one of the strategic steps in ensuring that every individual, including children with special needs, has equal opportunities to develop their potential. Isma Learning Therapy School (ILTS) is a curriculum model that focuses on empowering and developing the abilities of students with special needs in a boarding school environment. This study aims to analyze the development of social integration of students with special needs through the Isma Learning Therapy School (ILTS) curriculum at Ainul Yakin Islamic Boarding School. The method used is qualitative research with a case study approach. Data were collected through participatory observation, in-depth interviews with teachers, students, and parents, and document analysis related to curriculum implementation. The results of this study examine the curriculum of Isma Learning Therapy School (ILTS) at Pondok Pesantren Ainul Yakin, Yogyakarta, designed for students with special needs. The curriculum integrates therapeutic approaches and traditional education through observation, diagnosis, and customized learning. The results showed that the development of social integration in special needs students reached 75%, with an increase in social skills by 80% and a better attitude of independence by 90%. Key challenges include teacher training and community support. This study confirms the effectiveness of ILTS in creating an inclusive learning environment that supports the optimal development of santri. Overall, the ILTS curriculum has excellent potential but requires further collaborative efforts.